CREATIVITY AND INNOVATION OF DIGITAL ENTREPRENEURSHIP: A REVIEW OF LITERATURE FOR FUTURE RESEARCH AGENDA - Abdullah, Azizan (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Digital entrepreneurship emerges when Artificial Intelligent (AI) becoming important agenda to the world in the 2020s. The application of AI to the industries and society have a significant impact. Global economy has undergone dramatic changes due to advance technology introduced, everyday life, society and businesses. Hugh number of businesses in the world today used AI for better performance of their organization through creativity and innovation. These creativity and innovation work hand in hand through personnel, individual or groups to think a new way of solution for problem solving. It has been utilised continuously to generate ideas among entrepreneurs and their teams for new product creation or latest method of processing. Extensive research has been conducted on creativity and innovation by scholar; however, majority of the studies focused on traditional ways of stimulating both techniques. Such traditional ways include force analogy, lateral thinking, brainstorming, brainwriting, reverse brainstorming and mind mapping. Those kinds of approaches are insufficient in the digital era in which provides new business challenges. The traditional techniques of stimulating creativity are too slow, limited scope and struggle to match the speed and complexity of the market and environment. Thus, it has been replaced and aided by technology-driven innovations, such as internet of things (IoT), virtual reality (VR) and AI. The new innovations are changing technological entrepreneurship especially when it comes to new business creation processes. AI provide crucial implications of how entrepreneurs develop, strategize and growth their companies during the entrepreneurial processes. This system is able to empower entrepreneurs of creation new opportunities, introducing new products or services through digital entrepreneurial activities. Therefore, this paper aims to examine the role of Artificial Intelligent in enhancing creativity and innovation within digital entrepreneurship.